Ultra‐low dose CT colonography with automatic tube current modulation and sinogram‐affirmed iterative reconstruction: Effects on radiation exposure and image quality. Issue 1 (26th December 2018) - Cianci, Roberta; Delli Pizzi, Andrea; Esposito, Gianluigi; Timpani, Mauro; Tavoletta, Alessandra; Pulsone, Pierluigi; Basilico, Raffaella; Cotroneo, Antonio Raffaele; Filippone, Antonella
Abstract: Objective: To assess the radiation dose and image quality of ultra‐low dose (ULD)‐CT colonography (CTC) obtained with the combined use of automatic tube current (mAs) modulation with a quality reference mAs of 25 and sinogram‐affirmed iterative reconstruction (SAFIRE), compared to low‐dose (LD) CTC acquired with a quality reference mAs of 55 and reconstructed with filtered back projection (FBP). Methods: Eighty‐two patients underwent ULD‐CTC acquisition in prone position and LD‐CTC acquisition in supine position. Both ULD‐CTC and LD‐CTC protocols were compared in terms of radiation dose [weighted volume computed tomography dose index (CTDIvol ) and effective dose], image noise, image quality, and polyp detection. Results: The mean effective dose of ULD‐CTC was significantly lower than that of LD‐CTC (0.98 and 2.69 mSv respectively, P < 0.0001) with an overall dose reduction of 63.2%. Image noise was comparable between ULD‐CTC and LD‐CTC (28.6 and 29.8 respectively, P = 0.09). There was no relevant difference when comparing image quality scores and polyp detection for both 2D and 3D images. Conclusion: ULD‐CTC allows to significantly reduce the radiation dose without meaningful image quality degradation compared to LD‐CTC.